Phaeochromocytoma in a coeliac ganglion in pregnancy. Issue 703 (May 1984) - Parsons, J.; Clunie, R. W. D.; Letchworth, A. T.
Abstract : A case of a phaeochromocytoma is reported which presented as collapse in the postpartum period. The site of the tumour was in the coeliac ganglion.